Modeling soil detachment capacity by rill flow under the effect of freeze–thaw and the root system - Ma, Jianye; Li, Zhanbin; Sun, Baoyang; Ma, Bo; Zhang, Letao (Natural hazards (Dordrecht), 2022)
Freeze–thaw has a significant impact on soil detachment in areas subject to seasonal freeze–thaw. Plant root system has gradually played a key role in reducing soil detachment, with the implementation of a series of ecological restoration projects. However, few studies were conducted to evaluate soil detachment process under the combined effect of freeze–thaw and root system. This study investigated the potential effects of freeze–thaw and the root system on soil detachment capacity. Soil detachment capacity of two soil types, sandy loam and silt loam, was investigated, under four treatments, control (bare soil without freeze–thaw and root), freeze–thaw, root system and freeze–thaw + root system. A prediction model was developed to calculate soil detachment capacity under the effect of freeze–thaw and the root system. Hydraulic flume experiments were carried out at 4 flow rate (6–24L·min −1 ) and 1 slope (10°). The results illustrated that the detachment capacity of sandy loam was higher than that of silt loam. The soil detachment capacity of two soils was reduced and increased by the root system and freeze–thaw, respectively, although the former effect was significant ( P < 0.05) whereas the latter was not. The effect of freeze–thaw in combination with the root system showed that the root system contributed the majority of soil detachment capacity variability; therefore, the root system played a leading role in the inhibition of soil detachment capacity. When comparing shear stress, unit energy of the water carrying section and unit stream power, stream power was found to be the hydraulic parameter that best predicted soil detachment capacity ( R 2 > 0.84). The inclusion of root weight density significantly improve the accuracy of the soil detachment capacity prediction model developed by hydraulic parameters. A general model based on stream power and root weight density was developed to quantify soil detachment capacity and was shown to have a high soil detachment capacity prediction accuracy for both soils treated by freeze–thaw and the root system [ NSE = 0.88, R 2 = 0.90].